A high frequency phase reference - Panagi, Georgios; Patz, Ralf; Watson, S.; Kalogirou, Soteris A.; Williams, Robert J. (My University, 2004)
Magnetic Induction Tomography (MIT) requires signal measurements with a very high degree of phase precision. To enable the development and characterisation of input amplifiers, signal distribution and signal measurement system for MIT, a high precision phase reference capable of operating over the frequency range DC - 50 MHz is being developed. The phase reference consists of two Direct Digital Synthesizers (DDS) which are supplied with a common clock and control bus. The synthesizers are programmable, allowing 14-bit resolution (20 m°) of the phase offset between the channels and 12-bit control of the output amplitude (8Vpp max). The phase reference is controlled by a PC via a USB interface. Details of the design of the phase reference and the results of measurements of the phase noise, phase drift and phase skew performance of the system is given.
Keywords: Magnetic Induction Tomography; Direct Digital Synthesis; Phase Reference